Creep recovery of prepacked aggregate concrete - Abdul Awal, A. S. M. (American Society of Civil Engineers, 1992)
Previously the writer presented the results of a study on the creep and shrinkage behavior of prepacked aggregate concrete. In the same study strain on removal of sustained load was also measured. In this article, results on creep recovery of normal and prepacked aggregate concrete are presented and discussed. It has been observed that the creep recovery of prepacked aggregate concrete is lower than that of normal concrete